2020
DOI: 10.25165/j.ijabe.20201304.4826
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for identifying wheat leaf disease images based on differential amplification convolutional neural network

Abstract: In this study, a differential amplification convolutional neural network (DACNN) was proposed and used in the identification of wheat leaf disease images with ideal accuracy. The branches added between the deep convolutional layers can amplify small differences between the real output and the expected output, which made the weight updating more sensitive to the light errors return in the backpropagation pass and significantly improved the fitting capability. Firstly, since there is no large-scale wheat leaf di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The deep learning model Differential Amplification Convolutional Neural Network (DACNN) proposed to recognize these diseases by combined capabilities of four classifiers Support Vector Machine, Random forest, Softmax and K-Nearest Neighbor (KNN). The proposed model accuracy is 95.18% which is highest among Inception v3, ZFNet, LeNet and Alexnet models [76]. The diagnosis and recognition of the leaves diseases portray the status of the crop.…”
Section: Wheatmentioning
confidence: 88%
“…The deep learning model Differential Amplification Convolutional Neural Network (DACNN) proposed to recognize these diseases by combined capabilities of four classifiers Support Vector Machine, Random forest, Softmax and K-Nearest Neighbor (KNN). The proposed model accuracy is 95.18% which is highest among Inception v3, ZFNet, LeNet and Alexnet models [76]. The diagnosis and recognition of the leaves diseases portray the status of the crop.…”
Section: Wheatmentioning
confidence: 88%
“…In a number of real-world applications, the isotropic assumption is false and does not accurately reflect the probable connection between the sample's dimensional components. [13][14][15][16] As a result of the growth of artificial intelligence [14], image processing and classification research makes substantial use of deep learning techniques [15]. Dong et al [14] suggested use a convolutionl neural network with differential amplification to identify wheat diseases.…”
Section: Literature Surveymentioning
confidence: 99%
“…[13][14][15][16] As a result of the growth of artificial intelligence [14], image processing and classification research makes substantial use of deep learning techniques [15]. Dong et al [14] suggested use a convolutionl neural network with differential amplification to identify wheat diseases. Its average identification accuracy increased by 6.03 percent compared to LeNet-5.…”
Section: Literature Surveymentioning
confidence: 99%
“…Therefore, machine learning techniques achieve low classification accuracy as compared to deep learning techniques for wheat rust disease identification [14], [15]. hybrid models have been developed (CNN-LSVM [16] and Differential amplification CNN (DACNN) [17] for wheat rust disease identification. After the classification of crop diseases [18], [19] different severity levels of diseases are identified at a large scale.…”
Section: Introductionmentioning
confidence: 99%